Management of Food Waste by Using GIS Environment: A Review - Hitesh V, Raut; Ajay D, Nagne; Karbhari V, Kale (International Journal of Computer Sciences and Engineering, 2025)
A problem of food waste becomes a critical issue and achieving won’t be easy because of growing population and increasing urbanization. It affects the social and environmental problem. Every time food is wasted the other sources like water, energy, time, manpower, land, fertilizer, packaging and mainly money is also wasted. Waste has to paid twice once in the form of packaging and again for disposal. In food waste management collection of waste food from bins plays a crucial role and how it is reduce, reuse and recycling. This paper proposes a discussion about role of geographic information system in management of food waste and its use in collection of waste food for reuse, recycling and reduction in waste and optimization of waste food collection and transport.